Analysis of elementary school teachers’ perspectives on stem implementation - Diah Susanti; Zuhdan Kun Prasetyo; Heri Retnawati (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2020)
The approach of Science, Technology, Engineering, and Mathematics (STEM) in Indonesia is a new thing in education. The actors in the world of education still continue to adapt to all changes and updates happened all the time. Yet, sometimes the changes are not supported by the improvement in teachers’ knowledge, skill, and readiness. This phenomenological research aims to analyze the elementary teachers' perspective in Science, Technology, Engineering, Mathematics (STEM) framework implementation in Indonesia. The research is phenomenological research focused on the elementary school teachers’ perspective on STEM implementation. There are 35 teachers of public and private elementary schools with more than a year of service period in Yogyakarta, Indonesia was involved in this research. Data collection was conducted by the interview. The data collecting technique was analyzed with Bogdan and Biklen's analysis models. The analysis results were used to seek the information related to the following aspects: Teachers’ knowledge of STEM, benefits of STEM, steps of STEM implementation, assessment of STEM implementation, and teacher readiness to implement STEM. The results showed that the teachers’ knowledge in the STEM framework was still low and they were not ready to implement STEM for various reasons. This research is expected to be a reference for elementary schools and local government in socializing STEM and to support the STEM implementation in elementary schools.